Key recent advances in TB vaccine development and understanding of protective immune responses against mycobacterium tuberculosis (2020)
Tuberculosis is the leading infectious disease killer globally due to a single pathogen. Despite wide deployment of standard drug regimens, modern diagnostics and a vaccine (bacille Calmette Guerin, BCG), the global tuberculosis epidemic is inadequately controlled. Novel, effective vaccine(s) are a crucial element of the World Health Organization End TB Strategy. TB vaccine research and development has recently been catalysed by several factors, including a revised strategy focused first on preventing pulmonary TB in adolescents and adults who are the main source of transmission, and encouraging evaluations of novel efficacy endpoints. Renewed enthusiasm for TB vaccine research has also been stimulated by recent preclinical and clinical advancements. These include new insights into underlying protective immune responses, including potential roles for ‘trained’ innate immunity and Th1/Th17 CD4+ (and CD8+) T cells. The field has been further reinvigorated by two positive proof of concept efficacy trials: one evaluating a potential new use of BCG in preventing high risk populations from sustained Mycobacterium tuberculosis infection and the second evaluating a novel, adjuvanted, recombinant protein vaccine candidate (M72/AS01E) for prevention of disease in adults already infected. Fourteen additional candidates are currently in various phases of clinical evaluation and multiple approaches to next generation vaccines are in discovery and preclinical development. The two positive efficacy trials and recent studies in nonhuman primates have enabled the first opportunities to discover candidate vaccine-induced correlates of protection, an effort being undertaken by a broad research consortium.